Inclusive and Consequential by Design: "Futurefying" New Product Development (NPD) Through Vision Concepting. Issue 3 (12th November 2019) - Winchester, Woodrow W.
ABSTRACT: "As technology becomes more ubiquitous, it is essential we consider the impacts on people, whether unintended consequences or designs that exclude certain groups or disadvantage them in some way, " states Mark Searle, executive vice president of Arizona State in the New York Times article "Top Universities Join to Push 'Public Interest Technology' (Singer 2019)." As such, more inclusive and consequential approaches to New Product Development (NPD) are needed. This article introduces Vision Enabled Design Thinking (V.E.D.T) as a pathway forward. V.E.D.T incorporates the power of futures thinking, engaged through vision concepting, in the creation and evaluation of future‐forward design deliverables and artifacts in catalyzing more inclusive and consequential near‐term design solutions. A case study is also presented that highlights the use of V.E.D.T in the design of more inclusive wearable health technologies. Discussion is also had that advocates for more active systems engineering involvement in developing more inclusive and sustainable NPD practices and processes.